Temperature Gradient Gel Electrophoresis as a Valuable Accessory Tool for Assessment of Dysbiosis in Crohn's Disease - Carvalho, Vanessa Rafaela de [UNESP]; Keller, Rogeria [UNESP]; Silva Santos, Ana Carolina da [UNESP]; Rodrigues, Josias [UNESP] (Hans Publishers, 2016)
Escherichia coli and other Proteobacteria are augmented and several other bacteria are diminished in Crohn's (CD) disease patients' intestine. This imbalance in bacterial species composition-termed dysbiosis-seems to be determinant of CD manifestation. Since a great part of intestinal bacteria are not cultivable, detection of CD dysbiosis is accomplished by molecular tools, involving sequences analysis of the 16SrRNA gene (16SrDNA) present in the patient's clinical samples, which can be done by sequencing or electrophoresis in denaturing gels of 16SrDNA amplicons. By analyzing, by temperature gradient gel electrophoresis (TGGE) and next generation sequencing of 16SV6-V8rDNA amplicons present in gram negative cultures from four distinct clinical samples of a control subject and a CD patient, this study demonstrates that both techniques were able to detect E. coli over-growth and reduction in species richness in CD and that TGGE can discriminate sequences collectively labeled as unclassified in 16SrDNA databases. Although TGGE per se does not identify the sequences, the discriminatory power that it confers represents valuable accessory information to next generation DNA sequencing (NGS), and as such must be used as a NGS complementary tool.
Keywords: Dysbiosis; Proteobacteria; Escherichia coli; Crohn's Disease